Perception and Attitude Changes of Stakeholders for Resilient City Policy by Online Deliberation - Baba, Kenshi; Amanuma, Eri; Iwami, Asako (Frontiers in Sustainable Cities, 2021)
The aim of this study is to clarify the stakeholders' perceptions and attitudes of climate change adaptation in disaster prevention, which is one of the essential factors to make cities resilient, with the expert knowledge and discussion with each other participant via online deliberative experiment. We set up online virtual communities consisting of stakeholders living in disaster-stricken cities and towns who are expected to have a certain stake in this issue, and conducted a deliberation within the communities for 14 days on resilient city policy focusing on climate change adaptation in disaster risk reduction with the relevant knowledge from experts. We then analyzed changes of the perceptions and attitudes of the participants using the utterances (text data on the message boards) and the questionnaire data of before and after deliberation. The main results are as follows; i) during the deliberation, a wide range of topics were discussed and converged to policy options over time, ii) health damage and wind and flood damage were rated high before and after the deliberation as climate change risk, and especially water shortage and deterioration of water was got rated high after the experiment, iii) the self-help measures were got understanding of the participants though transformative measures including evacuation for a long time faced negative responses. almost none of the adaptation policies received greater opposition after deliberations than before, participants gained, through discussion, a deeper understanding of measures they themselves could implement (self-help) especially, iv) perceived effectiveness of adaptation policies have been improved after deliberation, though, cost-benefit evaluation for transformative measures was remarkably lower after deliberation, that is, they will be difficult to implement. Therefore, we need to provide expert knowledge which can make people change their framing.